A Grammar of Kam Revealed in Its Narrative Discourse - Yang, Tongyin (Springer Singapore : Imprint: Springer, 2017)
The Kam language of China possesses fifteen tones - more than any other language. Yet it has long been neglected as an area of research, especially from the perspective of discourse analysis. This study initiates the exploration of the interface between grammar and discourse by examining various aspects of Kam narrative discourse, and using a functional approach to reveal its structural properties. It also introduces the mechanism for phonological and syntactic variations, as well as classifier variants and sentence-final particles (SFPs) in discourse and word order variations. Finally, it discusses the influence of social setting on narrative structure and offers the most up-to-date ethnological and social information about the community.
Keywords: Linguistics.; Languages.; Language and languages.; Cultural studies.; elektronické knihy; electronic books